A Review of the Literature on Smart Development: Lessons for Small Municipalities - Å ipilova, Viktorija; Ostrovska, Inta; Aleksejeva, Ludmila; Jermolajeva, Elita; OÄ¼ehnoviÄs, Dmitrijs (International Journal of Economics and Financial Issues, 2017)
Nowadays, scientists and practitioners unify modern regional development under the term “smart”, what brings technologies and creation of a new knowledge in a front of economic activities. Small municipalities as participants of the process have been studied seldom. Moreover, a huge part of the literature on smart development mostly pays attention to such key elements, which have limited capabilities in small municipalities (e.g. development of high technologies, patent activities, sustainability etc.). Thus, involvement of small municipalities into the process of smart development may be slowed-up, due to their insufficient knowledge and experience. This paper offers a literature review on scientific findings and practical guides about smart development with aim to show how small municipalities could develop “smartly” in bigger extent. The research results highlight scientifically proved cornerstones of smart development and provide analysis of successful experience, how small municipalities can apply it in a practice. Keywords: smart development, small municipalities JEL Classifications: O11, O18, O21